(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2011)
Abstract The Ministry of Religious Affairs cooperates with the Government of Australia had built an Islamic Junior High School-One Ceiling Program (MTs-SA) amid the rural community in suburb area. The development of the Mts-SA aims at improving primary education access in the course of supporting an accomplishment for obligatory study and of improving graduation quality at private education institution managed by community group as classified poor or geographically isolated. This writing explains the educayional access development, management, and community participation in supporting the existence of MTs-SA. Â Abstrak Kementrian Agama bekerja sama dengan Pemerintah Australia telah membangun Madrasah Tsanawiyah SA (MTs-SA) di tengah masyarakat pedesaan di wilayah pinggiran. Pembangunan MTs-SA bertujuan untuk meningkatkan akses pendidikan dasar dalam rangka mendukung penyelesaian wajib belajar, serta peningkatan kualitas lulusan pada lembaga pendidikan swasta yang dikelola oleh kelompok masyarakat yang tergolong miskin atau secara terisolasi secara geografis. Tulisan ini menjelaskan pengembangan akses pendidikan, tata kelola, dan partisipasi masyarakat dalam mendukung keberadaan MTs-SA.